PENGEMBANGAN MEDIA PEMBELAJARAN GEOBOARD MATERI SEGI EMPAT PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PENALARAN MATEMATIS SISWA DI SEKOLAH DASAR - Nuva Nurul Laiyinah; Sulianto, Joko; Mandar Sary, Ryky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background that drives this research is based on a preliminary study conducted by the researcher, namely teachers using learning media that are easy to find and simple. When the material is flat shapes, the teacher uses folded paper. While there are 13 students who said when the teacher teaches using learning media in the form of a protractor and ruler. This makes the researcher want to develop learning media. The purpose of this study is (1) to identify whether it is valid or not, (2) to find out whether it is practical or not, and (3) to identify whether or not the geoboard learning media is effective for quadrilateral material in mathematics learning to improve students' mathematical reasoning. This type of research is research and development According to Borg and Gall (1983) there are 10 steps. However, the researcher limits 6 steps including (1) Research and collection of initial information, (2) Planning, (3) Development of initial product format, (4) Initial trial, (5) Product revision, and (6) Field trial. Based on the results of the research and development of geoboard learning media (1) The development of learning media obtained valid results from the media expert validator 89%, material experts 90%, and material experts on the question instrument 89% with the criteria "Very valid", (2) The development of learning media obtained practical results from 3 teachers 93% and student response questionnaires 90.66% with the criteria "Very practical", and (3) The development of learning media obtained quite effective results from increasing students' mathematical reasoning obtained by 68% with the criteria "Quite effective". Based on the results of the study, it can be seen that the geoboard learning media for quadrilateral material in mathematics learning to improve students' mathematical reasoning in elementary schools meets the criteria of very valid, practical and quite effective.